Renal intercalated cells sense and mediate inflammation via the P2Y14 receptor. - Anie Azroyan; Virna Cortez-Retamozo; Richard Bouley; Rachel Liberman; Ye Chun Ruan; Evgeny Kiselev; Kenneth A Jacobson; Mikael J Pittet; Dennis Brown; Sylvie Breton (PLoS ONE)
Uncontrolled inflammation is one of the leading causes of kidney failure. Pro-inflammatory responses can occur in the absence of infection, a process called sterile inflammation. Here we show that the purinergic receptor P2Y14 (GPR105) is specifically and highly expressed in collecting duct intercalated cells (ICs) and mediates sterile inflammation in the kidney. P2Y14 is activated by UDP-glucose, a damage-associated molecular pattern molecule (DAMP) released by injured cells. We found that UDP-glucose increases pro-inflammatory chemokine expression in ICs as well as MDCK-C11 cells, and UDP-glucose activates the MEK1/2-ERK1/2 pathway in MDCK-C11 cells. These effects were prevented following inhibition of P2Y14 with the small molecule PPTN. Tail vein injection of mice with UDP-glucose induced the recruitment of neutrophils to the renal medulla. This study identifies ICs as novel sensors, mediators and effectors of inflammation in the kidney via P2Y14.